Understanding Emotions in Adolescents: Validation of the Indonesian Version of the Adolescent Alexithymia Scale - Kurniawan, Michelle Aveline; Sampe Tondok, Marselius (Kuras Institute, 2024)
Adolescence, marked by significant changes, often leads to emotional tension and instability associated with alexithymia. This study aimed to validate the Indonesian version of the Adolescent Alexithymia Scale, hypothesizing that its internal structure was unidimensional. Participants included 70 adolescents aged 13 to 18 years (M_age = 16.44; SD = 1.44). Data were collected using the Indonesian version of the Adolescent Alexithymia Scale, consisting of 24 items representing the four alexithymia indicators. The results revealed that the scale has a unidimensional internal structure, with 11 valid items, and sufficient validity and reliability coefficients. These items collectively represent the four main characteristics of alexithymia. The most dominant indicator is the difficulty in identifying and distinguishing between feelings and emotional bodily sensations. This research implies that this scale needs to be tested on different populations and in different contexts.